Hypermethylation of OPRM1: Deregulation of the Endogenous Opioid Pathway in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and Fibromyalgia - Wyns, Arne; Hendrix, Jolien; Van Campenhout, Jente; Buntinx, Yanthe; Xiong, Huan-Yu; De Bruyne, Elke; Godderis, Lode; Nijs, Jo; Rice, David; Chiang, Daniel; Polli, Andrea (MDPI AG, 2026)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and fibromyalgia (FM) are debilitating disorders with overlapping symptoms such as chronic pain and fatigue. Dysregulation of the endogenous opioid system, particularly µ-opioid receptor function, may contribute to their pathophysiology. This study examined whether epigenetic modifications, specifically µ-opioid receptor 1 gene (OPRM1) promoter methylation, play a role in this dysfunction. Using a repeated-measures design, 28 ME/CFS/FM patients and 26 matched healthy controls visited the hospital twice within four days. Assessments included blood sampling for epigenetic analysis, a clinical questionnaire battery, and quantitative sensory testing (QST). Global DNA (hydroxy)methylation was quantified via liquid chromatography-tandem mass spectrometry, and targeted pyrosequencing was performed on promoter regions of OPRM1, COMT, and BDNF. ME/CFS/FM patients reported significantly worse symptom outcomes. No differences in global (hydroxy)methylation were found. Patients showed significantly higher OPRM1 promoter methylation, which remained after adjusting for symptom severity and QST findings. Across timepoints, OPRM1 methylation consistently correlated with BDNF Promoter I and Exon III methylation. This is, to the best of our knowledge, the first study examining OPRM1 methylation in ME/CFS/FM. Increased OPRM1 methylation in patients, independent of symptoms or pain sensitivity measures, supports the hypothesis of dysregulated opioidergic signaling in these conditions.
Keywords: OPRM1; bisulfite conversion; descending modulation; epigenetics; fibromyalgia; myalgic encephalomyelitis/chronic fatigue syndrome; opioids; 3101 Biochemistry and Cell Biology; 31 Biological Sciences; 3404 Medicinal and Biomolecular Chemistry; 34 Chemical Sciences; 3107 Microbiology; Minority Health; Health Disparities and Racial or Ethnic Minority Health Research; Pain Research; Chronic Fatigue Syndrome (ME/CFS); Clinical Research; Health Disparities; Opioids; Fibromyalgia; Genetics; Women's Health; Neurosciences; Chronic Pain; 2.1 Biological and endogenous factors; Disputed aetiology and other; 0399 Other Chemical Sciences; 0604 Genetics; 0699 Other Biological Sciences; Chemical Physics; 3101 Biochemistry and cell biology; 3107 Microbiology; 3404 Medicinal and biomolecular chemistry; Humans; Fatigue Syndrome, Chronic; Receptors, Opioid, mu; DNA Methylation; Female; Fibromyalgia; Male; Middle Aged; Adult; Promoter Regions, Genetic; Epigenesis, Genetic; Brain-Derived Neurotrophic Factor; Case-Control Studies